Analisis Perputaran Modal Kerja Terhadap Laba Usaha Pada Koperasi Pegawai Republik Indonesia (Kp-Ri) Tekad Waras Dinas Pendidikan Dan Kebudayaan Kabupaten Lebak-Rangkasbitung - Herni Handayani; Dedi Daryanto (FEB Universitas Sultan Ageng Tirtayasa, 2016)
This research aims to know the working capital turnover and operating income/profitabiltas (return on assets) in the Republic of Indonesia Employees Cooperative (KP-RI) Determination Sane education service and culture Districts of Lebak-Rangkasbitung, also to find out how much influence turnaround working capital and business profit/profitabiltas (return on assets) in the Republic of Indonesia Employees Cooperative (KP-RI) Determination Sane education service and culture Districts of Lebak-Rangkasbitung. As for the method used is descriptive method quantitative and assosiatif which later in sports and in the analysis of conclusion to be taken. From the test results can be known that there is a strong link between the working capital turnover with business profit/profitability (return on assets) due to the rotation of the working capital is able to explain the changes that occurred on the profitability of the remaining 22.9% and 77.1% influenced factors other than working capital turnover.